Comercio interregional e integracion comercial en el Caribe : el comercio de Puerto Rico con la region. - Castaner, Juan A. (1990)
Given the growing interest to Puerto Rico of its links with the Caribbean, the article shows that the impact on this island of its exports to CARICOM is unimportant, except as regards textiles and the garment industry. Also shows the positive effect on Puerto Rico of the complimentary industrial plant policy now being implemented with the Dominican Republic.